COMPARATIVE ANALYSIS OF REGIONAL FINANCIAL PERFORMANCE IN THE PERIOD BEFORE AND DURING THE COVID-19 PANDEMIC DISTRICT/CITY IN CENTRAL JAVA PROVINCE - Mia Ardhi Nur Afifa; Nuwun Priyono (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This study aims to compare the financial performance of district/city governments in Central Java Province between before the pandemic and during the pandemic using financial ratio analysis. The Regency/City Budget and Expenditure Realization Report used in the 2018-2020 fiscal year is included in the secondary data used in this study. The method used is a descriptive quantitative. Based on the results of this study, it was concluded that the degree of decentralization of regencies/cities in Central Java Province before the pandemic and during the pandemic was still in the low category, meaning that the district/city governments were able to implement decentralization, however, the amount of local revenue was still relatively small compared to the total revenue. In the regions, the independence ratio has an instructive relationship pattern included in the very low category, while the effectiveness ratio and efficiency ratio are in the effective and efficient category.